Association of Midfacial Fractures with Ophthalmic Injury. Issue 2 (June 2017) - Politis, Constantinus; Kluyskens, Alexandra; Dormaar, Titiaan
The aim of this study is to evaluate the incidence of ophthalmic complications following midfacial fractures and investigate its relation to surgical or nonsurgical treatment. This article is a retrospective study, describing the spectrum and incidence of ophthalmic injury in 106 patients presenting with midfacial fractures at the Department of Oral and Maxillofacial Surgery of the University Hospitals Leuven over a period of 16 months (January 2013 to April 2014). The mean age of the patients was 45.6 years with a gender distribution of 68 men and 38 women. The main cause of trauma was road traffic accidents. Forty-one patients suffered an ophthalmic injury following the fracture. Twelve of them had a persistent ophthalmic problem. Ophthalmic examination is necessary during the initial management. The time window for preservation of sight is small and treatment should be started immediately. Development of an emergency trauma scale that includes fractures, symptoms of visual impairment, and patient history is recommended and should stimulate a multidisciplinary approach of complex cases.